Composite enhanced solid electrolyte membrane and preparation method thereof
By preparing a three-dimensional nanofiber membrane composite with a polymer electrolyte through electrospinning, the problems of insufficient mechanical strength and ionic conductivity of polymer-based solid electrolyte membranes are solved, realizing a composite electrolyte membrane with high safety and easy processing, and providing a stable electrolyte solution for lithium metal batteries.
Patent Information
- Application Number
- CN202511196557.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-26
- Publication Date
- 2025-11-14
AI Technical Summary
Single polymer-based solid electrolyte membranes are deficient in mechanical strength and room temperature ionic conductivity, and have poor compatibility with lithium metal interfaces, resulting in high interfacial impedance and interfacial thermodynamic instability, which pose safety hazards.
Three-dimensional nanofiber membranes were prepared by electrospinning and then formed into composite reinforced solid electrolyte membranes by liquid-phase composite film formation process with a mixture of polymer solid electrolyte and lithium salt. The rigid constraint of the three-dimensional nanofibers and the interfacial adhesion of the polymer were utilized to improve mechanical integrity and electrochemical stability.
It achieves high ionic conductivity and low interfacial resistance, with good interfacial compatibility and cycle stability, reduces the risk of lithium dendrite penetration, and improves battery safety and processability, making it suitable for lithium metal batteries.
Smart Images

Figure CN120955208A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of lithium battery electrolytes, specifically to a composite reinforced solid electrolyte membrane and its preparation method. Background Technology
[0002] With the increasing depletion of fossil fuels and the continued advancement of global policies to vigorously develop clean energy, new energy sources, represented by wind and solar power, have been widely adopted. However, the inherent intermittency and instability of these energy sources severely restrict their efficient utilization. Against this backdrop, energy storage technology, especially chemical energy storage devices—batteries—has become crucial for improving the grid integration and absorption capacity of new energy sources and the stability of the power grid. Among numerous battery systems, lithium-ion batteries and lithium metal batteries, with their potential for higher energy density, have become one of the most widely used and promising advanced battery technologies due to their excellent overall performance. Despite significant progress in lithium metal battery technology, its large-scale commercial application still faces a series of challenges, among which safety issues are a key constraint reducing public acceptance and hindering its wider application. The organic liquid electrolytes widely used in traditional liquid lithium batteries are generally flammable, volatile, and prone to leakage. When batteries encounter extreme conditions such as overcharging, over-discharging, short circuits, mechanical abuse (e.g., squeezing, puncture), or thermal runaway, the liquid electrolyte is highly susceptible to ignition or even explosion, posing serious safety hazards.
[0003] Solid-state electrolytes, by eliminating liquid components, fundamentally reduce the risk of combustion, bringing a milestone of hope for the development of high-safety lithium batteries. However, solid-state electrolytes generally face severe solid-solid interface problems: poor physical contact with the electrodes (especially lithium metal anodes) leads to extremely high interfacial impedance, and interfacial thermodynamic instability easily triggers continuous side reactions, making the interface a major bottleneck and research hotspot for improving solid-state battery performance. To address this interfacial challenge, polymer-based solid-state electrolytes, due to their excellent flexibility, good interfacial contact capabilities, and ease of solution processing, are considered a crucial breakthrough for improving solid-solid interface contact and reducing interfacial impedance. Compared to rigid inorganic solid-state electrolytes, polymer materials can adhere more tightly to the electrode surface (especially lithium metal anodes), providing more effective physical contact points, thus theoretically significantly reducing interfacial impedance. Furthermore, polymer electrolytes typically have a wider electrochemical window and better chemical stability, helping to suppress interfacial side reactions. However, polymer solid-state electrolytes have weak intrinsic mechanical strength and insufficient room-temperature ionic conductivity, making it difficult for a single film to simultaneously achieve high ionic conductivity, strong mechanical properties (dendrying suppression), and interfacial stability. Therefore, it is necessary to improve the bulk performance of polymer solid electrolytes while maintaining their interfacial advantages through material and structural optimization. Combining polymer solid electrolytes with high-strength, stable supporting substrates is a key strategy for achieving synergistic optimization and overcoming interfacial bottlenecks. Summary of the Invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the shortcomings of single polymer-based solid electrolyte membranes in terms of mechanical strength and room temperature ionic conductivity, thereby providing a composite solid electrolyte with high ionic conductivity (at room temperature), excellent mechanical strength, good thermal stability and compatibility with lithium metal interface through specific composite structure design, and an efficient preparation method thereof.
[0005] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:
[0006] A composite reinforced solid electrolyte membrane and its preparation method are disclosed, comprising a solid electrolyte, a lithium salt and a supporting substrate. The supporting substrate is a three-dimensional nanofiber membrane prepared by electrospinning. The membrane is prepared by liquid-phase composite film formation process by mixing a slurry of solid electrolyte and lithium salt with the three-dimensional nanofiber membrane.
[0007] The polymer solid electrolyte is one or more of the following: polycarbonate-based solid electrolytes such as polyvinyl carbonate-based solid electrolyte PVC, polyvinyl carbonate-based solid electrolyte PEC, polypropylene carbonate-based solid electrolyte PPC, polypropylene carbonate-based solid electrolyte PTMC, polyoxyethylene solid electrolyte, polysiloxane polymer electrolyte, and single lithium-ion conductive polymer electrolyte materials.
[0008] The lithium salt is one or more of LiTFSI, LiPF6, LiClO4, LiBF4, LiFSI, LiDFOB and LiBOB.
[0009] The raw materials for preparing the supporting substrate are polymeric materials such as polyimide (PI), polyethylene terephthalate (PET), cellulose nanofibers (CNF), and aramid nanofibers (ANF).
[0010] Furthermore, the liquid phase composite film formation process includes solution casting, wet coating, etc.
[0011] This invention also provides a composite reinforced solid electrolyte membrane and its preparation method, comprising the following steps:
[0012] Obtain a three-dimensional nanofiber membrane prepared by electrospinning;
[0013] A composite-reinforced solid electrolyte membrane was prepared by combining a slurry of solid electrolyte and lithium salt with a three-dimensional nanofiber membrane using a liquid-phase composite film formation process.
[0014] Furthermore, the specific steps of the preparation method for the solid electrolyte membrane obtained by the liquid-phase composite film formation process include:
[0015] S1. Three-dimensional nanofiber membrane material was prepared by electrospinning, and after vacuum drying, it was placed in a glove box filled with Ar for later use.
[0016] S2. A composite reinforced solid electrolyte membrane is obtained by liquid-phase composite film formation process of a mixed slurry of solid electrolyte and lithium salt, and then placed in a glove box filled with Ar to dry.
[0017] S3. Place the composite membrane loaded with slurry in a vacuum drying oven and dry it at 80℃ under vacuum for 12 hours to achieve complete solvent removal and polymer chain rearrangement curing, thereby obtaining a self-supporting composite solid electrolyte membrane.
[0018] Furthermore, in step S1, the coating parameters need to be adjusted depending on the electrospinning instrument used and the raw material of the supporting substrate.
[0019] Furthermore, the preparation method of the solid electrolyte material prepared in step S2 needs to be adjusted depending on the material.
[0020] Furthermore, the thickness of the electrospun diaphragm produced in step S1 is approximately 200–500 μm.
[0021] Furthermore, in step S2, the preparation process of the composite membrane requires loading the slurry onto the surface of the supporting substrate on both sides.
[0022] The technical solution of this invention has the following advantages:
[0023] 1. The present invention provides a composite reinforced solid electrolyte membrane. On the one hand, it uses an electrospun nanofiber membrane as a mechanical reinforcement framework and achieves in-situ composite formation of solid electrolyte slurry in three-dimensional pores through a liquid-phase composite film formation process, avoiding the ultra-high pressure molding required for brittle ceramic electrolytes and the resulting risk of interfacial contact failure. On the other hand, this design improves the mechanical integrity and electrochemical stability of the composite membrane through the rigid constraint of the three-dimensional nanofibers and the interfacial adhesion of the polymer, solving the core defect of flexible polymer electrolytes being easily penetrated by lithium dendrites, and providing a high-safety and easy-to-process electrolyte solution for solid-state batteries.
[0024] 2. The present invention provides a composite reinforced solid electrolyte membrane that addresses the side reaction problem between polymer electrolyte and lithium metal by innovatively using an electrospun nanofiber membrane as an isolation framework. Its three-dimensional network structure prevents direct contact between the polymer and lithium metal through physical steric hindrance effect, thereby reducing the occurrence of side reactions.
[0025] 3. The composite reinforced solid electrolyte membrane provided by this invention has high ionic conductivity and low interfacial resistance. When used as an electrolyte for lithium metal batteries, it exhibits good interfacial compatibility, cycle stability and safety reliability, providing a new feasible approach for the application of lithium metal batteries.
[0026] 4. This invention provides a composite-reinforced solid electrolyte membrane. Various types of three-dimensional nanofiber membranes are selected as substrates, and a polymer solid electrolyte is deposited onto the three-dimensional nanofiber substrate through a liquid-phase composite film-forming process to achieve uniform double-sided composite deposition. This method utilizes the porous structure of the substrate to achieve uniform electrolyte loading, and the material system is flexible and adjustable. The resulting composite membrane exhibits excellent cycle stability and interfacial compatibility, and the preparation process is simple, the raw materials are readily available, and the product structure has good uniformity, making it suitable for large-scale production. Attached Figure Description
[0027] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0028] Figure 1 This is an operation flowchart of Embodiments 1, 2, and 3 of the present invention, wherein the liquid phase composite film formation process used is solution casting, the polymer electrolyte raw material used is PPC, and the supporting substrate is PI.
[0029] Figure 2 These are electronic images of embodiments 1, 2, and 3 of this invention, which, from left to right, are PPC-2@PI-1, PPC-2@PI-2, and PPC-3@PI-1;
[0030] Figure 3 These are scanning electron microscope images of embodiments 1 and 2 of the present invention, from left to right: PI-1, PI-2 and PPC-2@PI-1;
[0031] Figure 4 These are the linear sweep voltammetry curves of Example 1 and Comparative Example 2 in this invention, wherein the electrochemical window obtained in Example 1 is significantly improved compared to that in Comparative Example 2;
[0032] Figure 5 This is the AC impedance spectrum of Example 1 in this invention, with a conductivity of approximately 2.346 × 10⁻⁶. -4 S cm -1 ;
[0033] Figure 6These are the symmetrical battery charge-discharge curves of Example 1 and Comparative Example 2 in this invention, wherein the critical current density obtained in Example 1 is significantly improved compared to Comparative Example 2.
[0034] Figure 7 The symmetrical battery charge-discharge curve of Embodiment 1 in this invention can achieve at least 600 hours of stable cycling.
[0035] Figure 8 The battery charge-discharge curve of Comparative Example 1 in this invention shows a short circuit after 120 hours of cycling. Detailed Implementation
[0036] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.
[0037] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.
[0038] Example 1
[0039] This embodiment provides a composite reinforced solid electrolyte membrane. The raw materials for preparing the solid electrolyte slurry are PPC and LiTFSI in a weight ratio of 2:1, and the raw material for preparing the three-dimensional nanofiber membrane is PI. The specific preparation method of the composite solid electrolyte membrane is as follows:
[0040] S1. Weigh 2.4g of PPC and 1.2g of LiTFSI powder and add 15ml of acetonitrile solvent. Stir magnetically at 800r / min in a glove box filled with Ar for 24h to fully dissolve and form a transparent and uniform slurry.
[0041] S2. 12wt% polyamic acid (solvent DMF:acetone = 3:1) was spun at 22kV with a feeding rate of 1.0mL / h and a receiving distance of 22cm, forming a PI nanofiber membrane after 4 hours. After stepwise imidization (80℃→280℃), a three-dimensional nanofiber substrate with a diameter of 200-500nm was obtained.
[0042] S3. In a glove box under an argon atmosphere, the uniform slurry obtained in step S1 is poured onto the PI electrospinning film on both sides, allowing the slurry to fully impregnate for 12 hours. Then, it is placed in a 60°C oven and vacuum dried for 24 hours to complete the composite process.
[0043] In this embodiment, the composite reinforced solid electrolyte membrane is obtained by loading polymer slurry on both sides of PI to form a PPC-2@PI-1 structure. The thickness of this composite solid electrolyte membrane is approximately 200 μm.
[0044] Example 2
[0045] This embodiment provides a composite reinforced solid electrolyte membrane. The raw materials for preparing the solid electrolyte slurry are PPC and LiTFSI in a weight ratio of 2:1, and the raw material for preparing the three-dimensional nanofiber membrane is PI. The specific preparation method of the composite solid electrolyte membrane is as follows:
[0046] S1. Weigh 2.4g of PPC and 1.2g of LiTFSI powder and add 15ml of acetonitrile solvent. Stir magnetically at 800r / min in a glove box filled with Ar for 24h to fully dissolve and form a transparent and uniform slurry.
[0047] S2. 18wt% polyamic acid (solvent DMF:acetone = 3:1) was spun at 16kV with a feeding rate of 1.0mL / h and a receiving distance of 14cm, forming a PI nanofiber membrane after 4 hours. After stepwise imidization (80℃→280℃), a three-dimensional nanofiber substrate with a diameter of 200-500nm was obtained.
[0048] S3. In a glove box under an argon atmosphere, the uniform slurry obtained in step S1 is poured onto the PI electrospinning film on both sides, allowing the slurry to fully impregnate for 12 hours. Then, it is placed in a 60°C oven and vacuum dried for 24 hours to complete the composite process.
[0049] In this embodiment, the composite reinforced solid electrolyte membrane is obtained by loading polymer slurry on both sides of PI to form a PPC-2@PI-2 structure. The thickness of the composite solid electrolyte membrane is approximately 300 μm.
[0050] Example 3
[0051] This embodiment provides a composite reinforced solid electrolyte membrane. The raw materials for preparing the solid electrolyte slurry are PPC and LiTFSI in a weight ratio of 3:1, and the raw material for preparing the three-dimensional nanofiber membrane is PI. The specific preparation method of the composite solid electrolyte membrane is as follows:
[0052] S1. Weigh 2.4g of PPC and 0.8g of LiTFSI powder and add 15ml of acetonitrile solvent. Stir magnetically at 800r / min in a glove box filled with Ar for 24h to fully dissolve and form a transparent and uniform slurry.
[0053] S2. 12wt% polyamic acid (solvent DMF:acetone = 3:1) was spun at 22kV with a feeding rate of 1.0mL / h and a receiving distance of 22cm, forming a PI nanofiber membrane after 4 hours. After stepwise imidization (80℃→280℃), a three-dimensional nanofiber substrate with a diameter of 200-500nm was obtained.
[0054] S3. In a glove box under an argon atmosphere, the uniform slurry obtained in step S1 is poured onto the PI electrospinning film on both sides, allowing the slurry to fully impregnate for 12 hours. Then, it is placed in a 60°C oven and vacuum dried for 24 hours to complete the composite process.
[0055] In this embodiment, the composite reinforced solid electrolyte membrane is obtained by loading polymer slurry on both sides of PI to form a PPC-3@PI-1 structure. The thickness of this composite solid electrolyte membrane is approximately 200 μm.
[0056] Example 4
[0057] This embodiment provides a composite reinforced solid electrolyte membrane. The raw materials for preparing the solid electrolyte slurry are PVDF and LiTFSI in a weight ratio of 2:1, and the raw material for preparing the three-dimensional nanofiber membrane is PI. The specific preparation method of the composite solid electrolyte membrane is as follows:
[0058] S1. Weigh 2.4g of PVDF and 1.2g of LiTFSI powder and add 15ml of N,N-dimethylformamide solvent. Stir magnetically at 800r / min in a glove box filled with Ar for 24h to fully dissolve and form a uniform slurry.
[0059] S2. 12wt% polyamic acid (solvent DMF:acetone = 3:1) was spun at 22kV with a feeding rate of 1.0mL / h and a receiving distance of 22cm, forming a PI nanofiber membrane after 4 hours. After stepwise imidization (80℃→280℃), a three-dimensional nanofiber substrate with a diameter of 200-500nm was obtained.
[0060] S3. In an argon-atmospheric glove box, the uniform slurry obtained in step S1 is poured onto the PI electrospinning film on both sides, allowing the slurry to fully impregnate for 12 hours. Then, it is placed in an 80℃ oven and vacuum dried for 24 hours to complete the composite process.
[0061] In this embodiment, the composite reinforced solid electrolyte membrane is obtained by loading polymer slurry on both sides of PI to form a PVDF-2@PI-1 structure. The thickness of the composite solid electrolyte membrane is approximately 200 μm.
[0062] Example 5
[0063] This embodiment provides a composite reinforced solid electrolyte membrane. The raw materials for preparing the solid electrolyte slurry are PEC and LiTFSI in a weight ratio of 2:1, and the raw material for preparing the three-dimensional nanofiber membrane is PI. The specific preparation method of the composite solid electrolyte membrane is as follows:
[0064] S1. Weigh 2.4g of PEC and 1.2g of LiTFSI powder and add 15ml of acetonitrile solvent. Stir magnetically at 800r / min in a glove box filled with Ar for 24h to fully dissolve and form a transparent and uniform slurry.
[0065] S2. 12wt% polyamic acid (solvent DMF:acetone = 3:1) was spun at 22kV with a feeding rate of 1.0mL / h and a receiving distance of 22cm, forming a PI nanofiber membrane after 4 hours. After stepwise imidization (80℃→280℃), a three-dimensional nanofiber substrate with a diameter of 200-500nm was obtained.
[0066] S3. In a glove box under an argon atmosphere, the uniform slurry obtained in step S1 is poured onto the PI electrospinning film on both sides, allowing the slurry to fully impregnate for 12 hours. Then, it is placed in a 60°C oven and vacuum dried for 24 hours to complete the composite process.
[0067] In this embodiment, the composite reinforced solid electrolyte membrane is obtained by loading polymer slurry on both sides of PI to form a PEC-2@PI-1 structure. The thickness of this composite solid electrolyte membrane is approximately 300 μm.
[0068] Example 6
[0069] This embodiment provides a composite reinforced solid electrolyte membrane. The raw materials for preparing the solid electrolyte slurry are PVC and LiTFSI in a weight ratio of 2:1, and the raw material for preparing the three-dimensional nanofiber membrane is PI. The specific preparation method of the composite solid electrolyte membrane is as follows:
[0070] S1. Weigh 2.4g of PVC and 1.2g of LiTFSI powder and add 15ml of acetonitrile solvent. Stir magnetically at 800r / min in a glove box filled with Ar for 24h to fully dissolve and form a transparent and uniform slurry.
[0071] S2. 12wt% polyamic acid (solvent DMF:acetone = 3:1) was spun at 22kV with a feeding rate of 1.0mL / h and a receiving distance of 22cm, forming a PI nanofiber membrane after 4 hours. After stepwise imidization (80℃→280℃), a three-dimensional nanofiber substrate with a diameter of 200-500nm was obtained.
[0072] S3. In a glove box under an argon atmosphere, the uniform slurry obtained in step S1 is poured onto the PI electrospinning film on both sides, allowing the slurry to fully impregnate for 12 hours. Then, it is placed in a 60°C oven and vacuum dried for 24 hours to complete the composite process.
[0073] In this embodiment, the composite reinforced solid electrolyte membrane is obtained by loading polymer slurry on both sides of PI to form a PVC-2@PI-1 structure. The thickness of the composite solid electrolyte membrane is approximately 300 μm.
[0074] Example 7
[0075] This embodiment provides a composite reinforced solid electrolyte membrane. The raw materials for preparing the solid electrolyte slurry are PPC and LiTFSI in a weight ratio of 2:1, and the raw material for preparing the three-dimensional nanofiber membrane is PET. The specific preparation method of the composite solid electrolyte membrane is as follows:
[0076] S1. Weigh 2.4g of PPC and 1.2g of LiTFSI powder and add 15ml of acetonitrile solvent. Stir magnetically at 800r / min in a glove box filled with Ar for 24h to fully dissolve and form a transparent and uniform slurry.
[0077] S2. Dissolve PET particles in hexafluoroisopropanol (20wt%) and heat at 60°C with stirring until completely dissolved. Extrude at a rate of 0.8 mL / h under a high voltage of 25 kV, with a receiving distance of 18 cm, to form a fiber membrane with a diameter of 300-800 nm.
[0078] S3. In an argon-atmospheric glove box, the uniform slurry obtained in step S1 is poured onto the PET electrospun film on both sides, allowing the slurry to fully impregnate for 12 hours. Then, it is placed in a 60°C oven and vacuum dried for 24 hours to complete the composite process.
[0079] In this embodiment, the composite reinforced solid electrolyte membrane is obtained by loading polymer slurry onto both sides of PET to form a PPC-2@PET structure. The thickness of the composite solid electrolyte membrane is approximately 300 μm.
[0080] Example 8
[0081] This embodiment provides a composite reinforced solid electrolyte membrane. The raw materials for preparing the solid electrolyte slurry are PEC and LiTFSI in a weight ratio of 2:1, and the raw material for preparing the three-dimensional nanofiber membrane is PET. The specific preparation method of the composite solid electrolyte membrane is as follows:
[0082] S1. Weigh 2.4g of PEC and 1.2g of LiTFSI powder and add 15ml of acetonitrile solvent. Stir magnetically at 800r / min in a glove box filled with Ar for 24h to fully dissolve and form a transparent and uniform slurry.
[0083] S2. Dissolve PET particles in hexafluoroisopropanol (20wt%) and heat at 60°C with stirring until completely dissolved. Extrude at a rate of 0.8 mL / h under a high voltage of 25 kV, with a receiving distance of 18 cm, to form a fiber membrane with a diameter of 300-800 nm.
[0084] S3. In an argon-atmospheric glove box, the uniform slurry obtained in step S1 is poured onto the PEC electrospinning film on both sides, allowing the slurry to fully impregnate for 12 hours. Then, it is placed in a 60°C oven and vacuum dried for 24 hours to complete the composite process.
[0085] In this embodiment, the composite reinforced solid electrolyte membrane is obtained by loading polymer slurry onto both sides of PET to form a PEC-2@PET structure. The thickness of the composite solid electrolyte membrane is approximately 200 μm.
[0086] Example 9
[0087] This embodiment provides a composite reinforced solid electrolyte membrane. The raw materials for preparing the solid electrolyte slurry are PEC and LiTFSI in a weight ratio of 3:1, and the raw material for preparing the three-dimensional nanofiber membrane is PET. The specific preparation method of the composite solid electrolyte membrane is as follows:
[0088] S1. Weigh 2.4g of PEC and 0.8g of LiTFSI powder and add 15ml of acetonitrile solvent. Stir magnetically at 800r / min in a glove box filled with Ar for 24h to fully dissolve and form a transparent and uniform slurry.
[0089] S2. Dissolve PET particles in hexafluoroisopropanol (20wt%) and heat at 60°C with stirring until completely dissolved. Extrude at a rate of 0.8 mL / h under a high voltage of 25 kV, with a receiving distance of 18 cm, to form a fiber membrane with a diameter of 300-800 nm.
[0090] S3. In an argon-atmospheric glove box, the uniform slurry obtained in step S1 is poured onto the PEC electrospinning film on both sides, allowing the slurry to fully impregnate for 12 hours. Then, it is placed in a 60°C oven and vacuum dried for 24 hours to complete the composite process.
[0091] In this embodiment, the composite reinforced solid electrolyte membrane is obtained by loading polymer slurry onto both sides of PET to form a PEC-3@PET structure. The thickness of the composite solid electrolyte membrane is approximately 200 μm.
[0092] Comparative Example 1
[0093] This embodiment provides a composite reinforced solid electrolyte membrane. The raw materials for preparing the solid electrolyte slurry are PPC and LiTFSI in a weight ratio of 2:1. The specific preparation method of the composite solid electrolyte membrane is as follows:
[0094] S1. Weigh 2.4g of PPC and 1.2g of LiTFSI powder and add 15ml of acetonitrile solvent. Stir magnetically at 800r / min in a glove box filled with Ar for 24h to fully dissolve and form a transparent and uniform slurry.
[0095] S2. In a glove box under an argon atmosphere, the uniform slurry prepared in step S1 is poured onto a polytetrafluoroethylene plate on both sides, left to stand for 12 hours, and then placed in a 60°C oven for vacuum drying for 24 hours.
[0096] Comparative Example 2
[0097] This embodiment provides a composite reinforced solid electrolyte membrane. The raw materials for preparing the solid electrolyte slurry are PPC and LiTFSI in a weight ratio of 2:1, and the membrane material is PP. The specific preparation method of the composite solid electrolyte membrane is as follows:
[0098] S1. Weigh 2.4g of PPC and 1.2g of LiTFSI powder and add 15ml of acetonitrile solvent. Stir magnetically at 800r / min in a glove box filled with Ar for 24h to fully dissolve and form a transparent and uniform slurry.
[0099] S2. In an argon-atmospheric glove box, the uniform slurry obtained in step S1 is poured onto the PP diaphragm on both sides, allowing the slurry to fully impregnate for 12 hours. Then, it is placed in a 60°C oven and vacuum dried for 24 hours to complete the composite process.
[0100] In this embodiment, the composite reinforced solid electrolyte membrane is obtained by loading polymer slurry on both sides of PP to form a PPC@PP structure. The thickness of the composite solid electrolyte membrane is approximately 200 μm.
[0101] Experimental Example 1
[0102] Process flow: The process flow diagram of the composite reinforced solid electrolyte membrane implemented in Examples 1-9 is shown below. Figure 1 As shown, the designed process is simple and easy to implement.
[0103] Reference Figure 1 It is evident that this solves the core defect of flexible polymer electrolytes being easily penetrated by lithium dendrites, providing a high-safety and easy-to-process electrolyte solution for solid-state batteries.
[0104] Experimental Example 2
[0105] Morphological characterization: Electron images of the composite reinforced solid electrolyte membranes described in Examples 1, 2, and 3 are shown below. Figure 2 As shown. The morphology of the electrospun substrates PI-1 and PI-2 in Examples 1 and 2, as well as the morphology of the composite solid electrolyte membrane, were observed using scanning electron microscopy (SEM). The SEM results are shown in [Figure number missing]. Figure 3 .
[0106] Reference Figure 2 It can be seen that the PPC-2@PI-1, PPC-2@PI-2 and PPC-2@PI-1 composite solid electrolyte membranes are uniform and dense. Figure 3 The three-dimensional nanostructure of the PI film obtained by electrospinning is achieved by double-sided loading of a mixed slurry of PPC and LiTFSI using a solution casting method, resulting in a dense and uniform surface.
[0107] Experimental Example 3
[0108] LSV testing: Li / SS batteries were assembled using conventional methods, with solid electrolyte membranes obtained in Example 1 and Comparative Example 2, respectively. Linear sweep voltammetry was performed using electrochemical work, and the test results are as follows: Figure 4 As shown.
[0109] Reference Figure 4 Test data shows that, compared to commercial PP separators (electrochemical window of 4.2V), the electrochemical stability window of the composite electrolyte loaded on a three-dimensional nanofiber PI-based membrane is significantly improved to 4.8V (vs. Li / Li+), which can be used with high-voltage cathode materials such as lithium cobalt oxide (LCO) and high-nickel ternary (NCM811) (>4.5V), and has the potential for high-voltage solid-state battery applications.
[0110] EIS Testing: SS / SS symmetric cells were assembled using conventional methods. The solid electrolyte membrane was the material obtained in Example 1. Electrochemical impedance spectroscopy (EIS) was performed during electrochemical testing. The test results are as follows: Figure 5 As shown.
[0111] Reference Figure 5 Test data, measured at 25℃ with a frequency range of 0.1Hz-1 MHz (amplitude 10mV), showed that the bulk ionic conductivity of the composite solid electrolyte membrane in Example 1 was approximately 2.346 × 10⁻⁶. -4 S·cm -1 This confirms that the PI fiber skeleton constructs a continuous ion transport channel.
[0112] Test Example 4
[0113] Cyclic stability test: Li / Li symmetric batteries were assembled using the solid electrolyte membranes obtained in Example 1, Comparative Example 1, and Comparative Example 2 according to conventional methods. Charge-discharge cycle tests were conducted using a blue electric system. The test results are as follows: Figure 6 , 7 As shown in Figure 8:
[0114] Reference Figure 6 It can be seen that at 25℃, the current density increases from 0.1 to 3 mA / cm². -2When using the composite electrolyte assembled in Example 1, the Li / Li symmetric cell achieved a critical current density (CCD) of 2.8 mA·cm⁻¹. -2 Comparative Example 2 at 1.5 mA·cm -2 Voltage instability (interface failure characteristic) will then occur.
[0115] Reference Figure 7 and 8 It can be seen that at 25℃, the current density is 0.2 mA / cm². -2 When using the solid electrolyte membrane obtained in Example 1, the lithium-lithium symmetric battery assembled can cycle stably for 600 hours with voltage polarization below 50mV. However, the lithium-lithium symmetric battery assembled using the solid electrolyte membrane obtained in Comparative Example 1 exhibited a short circuit after 120 hours of cycling, demonstrating that the PI fiber skeleton significantly enhances dendrite suppression capabilities.
[0116] Reference Figure 1-8 This invention provides a composite solid-state electrolyte based on an electrospun substrate film, achieving uniform composite formation of the polymer electrolyte within a three-dimensional fiber network through a liquid-phase composite film-forming process. This design utilizes the fiber skeleton to enhance mechanical strength, significantly reducing electrode contact impedance and effectively suppressing lithium dendrite growth. The resulting composite film possesses both a wide electrochemical window and high interfacial stability, supporting high-voltage cathode applications. Furthermore, its solution processing technology is compatible with large-scale production, and it exhibits excellent thermal safety performance, providing a highly reliable electrolyte solution for solid-state batteries.
[0117] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A composite reinforced solid electrolyte membrane and its preparation method, characterized in that, Using electrospun nanofiber membranes as a three-dimensional reinforcing framework, a composite solid electrolyte membrane is formed by uniformly loading a mixture of polymer and lithium salt on both sides of a liquid-phase composite film-forming method and then drying and densifying it. The polymer solid electrolyte is one or more of the following: polycarbonate-based solid electrolytes such as polyvinyl carbonate-based solid electrolyte PVC, polyvinyl carbonate-based solid electrolyte PEC, polypropylene carbonate-based solid electrolyte PPC, polypropylene carbonate-based solid electrolyte PTMC, polyoxyethylene solid electrolyte, polysiloxane polymer electrolyte, and single lithium-ion conductive polymer electrolyte materials. The lithium salt is one or more of LiTFSI, LiPF6, LiClO4, LiBF4, LiFSI, LiDFOB and LiBOB. The raw materials for preparing the supporting substrate are polymeric materials such as polyimide (PI), polyethylene terephthalate (PET), cellulose nanofibers (CNF), and aramid nanofibers (ANF).
2. The composite reinforced solid electrolyte membrane and its preparation method according to claim 1, characterized in that, The preparation method employs a liquid-phase composite film-forming process (such as solution casting or wet coating) combined with a low-temperature curing step. This method is simple to operate and has low energy consumption. Furthermore, both the electrospinning base film and the solution coating process are compatible with existing battery production line equipment, facilitating large-scale commercial application.
3. The composite reinforced solid electrolyte membrane and its preparation method according to claim 2, characterized in that, The prepared composite solid electrolyte membrane significantly improves its anti-dendritic ability through the mechanical reinforcement of the three-dimensional nanofiber skeleton and the synergistic combination with the polymer electrolyte.
4. The composite reinforced solid electrolyte membrane and its preparation method according to any one of claims 1-3, characterized in that, Includes the following steps: Obtain a three-dimensional nanofiber membrane prepared by electrospinning; A composite-reinforced solid electrolyte membrane was prepared by combining a slurry of solid electrolyte and lithium salt with a three-dimensional nanofiber membrane using a liquid-phase composite film formation process.
5. The composite reinforced solid electrolyte membrane and its preparation method according to claim 4, characterized in that, The specific steps include: S1. Three-dimensional nanofiber membrane material was prepared by electrospinning, and after vacuum drying, it was placed in a glove box filled with Ar for later use. S2. A composite reinforced solid electrolyte membrane is obtained by liquid-phase composite film formation process of a mixed slurry of solid electrolyte and lithium salt, and then placed in a glove box filled with Ar to dry. S3. Place the composite membrane loaded with slurry in a vacuum drying oven and dry it at 60°C under vacuum for 12 hours to achieve complete solvent removal and polymer chain rearrangement curing, thereby obtaining a self-supporting composite solid electrolyte membrane.
6. A composite reinforced solid electrolyte membrane and its preparation method according to claim 4 or 5, characterized in that, In step S1, the coating parameters need to be adjusted depending on the electrospinning instrument used and the raw material of the supporting substrate.
7. The composite reinforced solid electrolyte membrane and its preparation method according to claims 4-6, characterized in that, The preparation method for the solid electrolyte material prepared in step S2 needs to be adjusted depending on the material.
8. A composite reinforced solid electrolyte membrane and its preparation method according to claims 4-7, characterized in that, The thickness of the electrospun diaphragm produced in step S1 is approximately 200–500 μm.
Citation Information
Cited By
Conductive and flame-retardant polymer solid electrolyte as well as preparation method and application thereof
CN122315055A